REDEFINING CHILDHOOD: ADDRESSING LEGAL INCONSISTENCIES AND THE ROLE OF TRANSITIONAL AGE IN JUVENILE JUSTICE - Supriadi, Moh.; Yuliana, Yuliana; Ghani, Mohamad Zulkifli Abdul (Masalah-Masalah Hukum, 2025)
Indonesia’s legal framework, grounded in civil law, predominantly utilizes statutes as its primary source of legal authority. Nonetheless, discrepancies in the definitions of legal terminology across different statutes have resulted in ambiguity, especially regarding the interpretation of the term “child.”  The varying definitions of “child” across the Criminal Code, the Civil Code, and other child protection laws contribute to legal ambiguity, particularly regarding the rights and protections available to children in conflict with the law. Law No. 11 of 2012, known as the Juvenile Criminal Justice System Law, specifies that a child is defined as an individual between the ages of 12 and 18. Additionally, it encompasses individuals aged 18 to 21 who have yet to fulfill their sentence. This inconsistency leads to uncertainty about the enforcement of legal penalties and the suitable correctional institutions for these individuals. This study seeks to examine the legal terminology related to “children in conflict with the law” within the framework of the Juvenile Criminal Justice System Law, with an emphasis on the consequences for their placement and rehabilitation in Juvenile Correctional Institutions and Youth Prisons. The study adopts an empirical-normative methodology, incorporating field interviews and document analysis as key components. The findings indicate that varying definitions of “child” create ambiguity in legal application, especially concerning rehabilitation and sanctioning processes. The research offers valuable insights by advocating for the adoption of the term “transitional age” to delineate the differences between children and adults. This would improve legal clarity, safeguard children’s rights, and guarantee rehabilitation programs that are specifically designed to meet their developmental requirements.